Psychological reasoning in infancy. [article]. - Baillargeon, Renee
Adults routinely make sense of others' actions by inferring the mental states that underlie these actions. Over the past two decades, developmental researchers have made significant advances in understanding the origins of this ability in infancy. This evidence indicates that when infants observe an agent act in a simple scene, they infer the agent's mental states and then use these mental states, together with a principle of rationality (and its corollaries of efficiency and consistency), to predict and interpret the agent's subsequent actions and to guide their own actions toward the agent. In this review, we first describe the initial demonstrations of infants' sensitivity to the efficiency and consistency principles. Next, we summarize what is known about infants' ability to reason about agents' motivational, epistemic, and counterfactual states. Finally, we consider alternative interpretations of these findings and discuss the current controversy about the relation between implicit and explicit psychological reasoning. -- (from the authors)
Keywords: Scott, Rose M; Bian, Lin; Infant cognition; Psychological reasoning; Theory of mind; Rationality; Agency; Mental states; False beliefs; Implicit reasoning